PERAN PENDIDIKAN AKIDAH AKHLAK BERBASIS TEKNOLOGI DALAM PEMBENTUKAN KARAKTER DAN ADAB SOSIAL SISWA SEKOLAH DASAR - Imam Muchlisin; Yuliana Fajar Nur Hidayati; Fatiha Azrul Shifan Fayzan (IAI Al Muhammad Cepu, 2025)
The advancement of digital technology has significantly transformed the field of education, including moral and religious (akidah akhlak) education in elementary schools. This study aims to examine how the use of technology can support the development of students’ character and social conduct. The method employed is a literature review by analyzing four key relevant journals. The findings show that digital media such as Islamic applications, educational videos, and moral value-based digital projects can enhance students’ understanding and application of moral values, including empathy, cooperation, and social awareness. However, the successful implementation of technology largely depends on teacher readiness, parental supervision, and the appropriate selection of materials. This study concludes that technology-based akidah akhlak education requires an adaptive approach to align with the goals of character formation in the digital era.